MABUK, JUDI DAN ZINA SEBAGAI ALASAN PERCERAIAN: KAJIAN NORMATIF TERHADAP Pasal 39 UU No. 1 Tahun 1974 - Priscila, Michel; Sidi Ahyar Wiraguna (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study examines divorce on the grounds of moral misconduct specifically habitual drunkenness, gambling, and adultery based on Article 39(2) of Law No. 1 of 1974 on Marriage and Article 116(f) of the Compilation of Islamic Law. Using a normative juridical approach and qualitative analysis, the research explores statutory provisions, court decisions, and factual cases. The findings reveal that such behaviors significantly disrupt marital harmony and are legally recognized as valid grounds for divorce. However, victims often face procedural and evidentiary challenges in court, particularly in presenting direct proof of misconduct. The study concludes that divorce due to moral deviation serves as a form of legal protection for victims in unhealthy marriages. Strengthening access to justice, improving legal literacy, and aligning legal norms with social realities are essential to ensure fair and effective protection.